2020
DOI: 10.1093/cid/ciaa1466
|View full text |Cite
|
Sign up to set email alerts
|

Compassionate Use of Remdesivir in Pregnant Women With Severe Coronavirus Disease 2019

Abstract: Background Remdesivir is efficacious for severe COVID-19 in adults, but data in pregnant women are limited. We describe outcomes in the first 86 pregnant women with severe COVID-19 who were treated with remdesivir. Methods Reported data span March 21 to June 16, 2020 for hospitalized pregnant women with PCR-confirmed SARS-CoV-2 infection and room air oxygen saturation ≤94% whose clinicians requested remdesivir through the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
100
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 18 publications
0
100
0
5
Order By: Relevance
“…On the other hand, other studies have found that SARS-CoV-2 infection during pregnancy could compromise its course, being frequently associated with a worse obstetric outcome if compared with unaffected women at the same gestational age [62,63]. According to recent scientific evidence, it seems that the presence of previous maternal risk factors; such as an age > 35 years, a BMI > 30, a chronic hypertension or a pre-existing diabetes could be responsible of a worse clinical course, leading to a higher rate of admission in intensity care unit (ICU) [19,64,65]. In our research we have excluded patients with a BMI > 30 and/or age > 45 years because we wanted to reduce the risk of other gestational comorbidities, like diabetes, hypertension and pre-eclampsia which could worsen the clinical course of the infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, other studies have found that SARS-CoV-2 infection during pregnancy could compromise its course, being frequently associated with a worse obstetric outcome if compared with unaffected women at the same gestational age [62,63]. According to recent scientific evidence, it seems that the presence of previous maternal risk factors; such as an age > 35 years, a BMI > 30, a chronic hypertension or a pre-existing diabetes could be responsible of a worse clinical course, leading to a higher rate of admission in intensity care unit (ICU) [19,64,65]. In our research we have excluded patients with a BMI > 30 and/or age > 45 years because we wanted to reduce the risk of other gestational comorbidities, like diabetes, hypertension and pre-eclampsia which could worsen the clinical course of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…She was treated with the therapeutic protocol for SARS-CoV-2 pneumonia of our hospital, including remdesivir immediately after delivery. Remdesivir was chosen because it has been recently approved by FDA as a promising and safe antiviral drug against SARS-CoV2 in patients with severe respiratory symptoms; indeed, there are some preliminary reports showing that it could be safe and well tolerated also in pregnancy [65].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant women not requiring invasive ventilation at baseline had the highest rates of recovery (98%) and shortest median time to recovery (5 days); among those women, 98% recovered and 95% were discharged. Treatment with remdesivir was well tolerated; no new safety signals were detected among pregnant patients ( 46 ). Overall, remdesivir should be used during pregnancy only if the potential benefit justifies the potential risks for mother and fetus.…”
Section: Special Populationsmentioning
confidence: 99%
“…However, there is insufficient evidence for its safety during pregnancy, mainly due to its unknown risk of transplacental transfer [ 55 , 56 ]. Most relevant trials have excluded pregnant and breastfeeding women, although high recovery rates were observed in pregnant women who received compassionate use of remdesivir [ 57 ]. Therefore, standard-of-care administration of remdesivir in pregnant women with COVID-19 should be currently avoided [ 42 , 56 ].…”
Section: Resultsmentioning
confidence: 99%